Post Earnings Announcement Drift on The JSE Top 40: A Study on Longer Term Holding Periods - Msutu, Yonela Neo (University of the Witwatersrand, Johannesburg, 2024)
This paper studies the existence of the post-earnings announcement drift (PEAD) on the JSE top 40. The sample period used was from 2000-2020. The measures of surprise earnings used in this paper were the standardised unexpected earnings (SUE) and the initial 2-day returns (IR). The existence of PEAD was determined using portfolios sorted half yearly by the surprise measure of which the high minus low quantile spread (QS) was computed. A cross- sectional regression is run to determine if firm characteristics affect the PEAD. Cumulative abnormal returns (CARs) were used as a proxy PEAD and computed using the market model. PEAD drift exists on the JSE top 40, and the QS was found to be persistent for a 480-day trading window for both surprise measures. The PEAD anomaly found by QS was robust to a subsample period and the method of CAR computation. The IR-sorted portfolios generally outperformed the SUE-sorted portfolios. The SUE portfolio coefficients were insignificant in cross-sectional regression, while IR coefficients were up to the 360-day trading window.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; post-earnings announcement drift (PEAD); JSE; SDG-8: Decent work and economic growth